Realizing a Civilized Urban Society through the Application of Al-Ghazali's Tasawwuf Teachings (A Study of the Taklim Assembly of Kitab Ihya 'Ulumuddin) - Mas’ud, Mas’ud; Asnawan, Asnawan; Dahri, Harapandi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The reinterpretation and contextualization of the spiritual value of Sufism will be more meaningful if it is applied in a practical way to social life. The concepts of Love, Sincerity, and Patience in Sufism become meaningful for people who are currently experiencing the emptiness of the heart. Through Sufistic values, urban communities can practice applicable spiritual values amid the increasingly complex dynamics of modern human life. The purpose of this study is to describe the Sufistic values taught in Imam Al-Ghazali’s Sufism teachings and the relationship between Sufistic values and social intelligence in urban communities. The research method employs a qualitative approach, utilizing a field study research design through an interactive model. Through this research, Imam Al-Ghazali’s Sufistic values are found to have a close relationship with social intelligence. Sufistic values are indirectly able to provide awareness to a person on how to communicate, relate, and interact with urban communities that have increasingly complex problems. So socializing and socializing are not easily influenced by negative things with the religious stigma that has an impact on one’s psychological side.